Improvement of autohydrogenotrophic nitrite reduction rate through optimization of pH and sodium bicarbonate dose in batch experiments - Ghafari, S.; Hasan, M.; Aroua, M.K. (Journal of Bioscience and Bioengineering, 2009)
Accumulation of nitrite intermediate in autohydrogenotrophic denitrification process has been a challenging difficulty to tackle. This study showed that further growth of "true denitrifying" bacteria and adaptation to nitrite led to a faster reduction of nitrite than nitrate as a solution to circumvent nitrite accumulation. Moreover, two effective parameters namely pH and bicarbonate dose were optimized in order to achieve a better reduction rate. Sodium bicarbonate dose ranging from 20 to 2000Â mg/L and pH in the range of 6.5-8.5 was selected to be examined employing 0.2Â g MLVSS/L of reacclimatized denitrifying bacteria. Eleven runs of experiments were designed considering the interactive effect of these two operative parameters. A fairly close reduction time less than 4.5Â h (> 22.22Â mg NO 2 —N/g MLVSS/h) was gained for the pH range between 7 and 8. The highest specific nitrite reduction rate at 25Â mg NO 2 —N/g MLVSS/h was achieved applying 1000Â mg NaHCO 3/L at pH 7.5 and 8. The pH was found to be the leading parameter and bicarbonate as the less effective parameter on nitrite reduction removal. Central composite design (CCD) and response surface design (RSM) were employed to develop a model as well as define the optimum condition. Using the experimental data, the developed quadratic model predicted optimum condition at pH 7.8 and sodium bicarbonate dose 1070Â mg/L upon which denitrifiers managed to accomplish reduction within 3.5Â h and attained the specific degradation rate of 28.57Â mg NO 2 —N/g MLVSS/h.